2007
DOI: 10.1016/j.electacta.2007.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Curvature enhanced adsorbate coverage mechanism for bottom-up superfilling and bump control in damascene processing

Abstract: This article was published in an Elsevier journal. The attached copy is furnished to the author for non-commercial research and education use, including for instruction at the author's institution, sharing with colleagues and providing to institution administration.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
118
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 40 publications
(146 reference statements)
4
118
0
Order By: Relevance
“…Moreover, based on the activation phenomenon of PEGpassivated electrode by SPS, a replacement effect was further added to fully describe the additive behavior. 46 Here we consider all three aspects, and the equation of CA is given by…”
Section: 43mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, based on the activation phenomenon of PEGpassivated electrode by SPS, a replacement effect was further added to fully describe the additive behavior. 46 Here we consider all three aspects, and the equation of CA is given by…”
Section: 43mentioning
confidence: 99%
“…Follow the same definition of transition time, t trans2 (1.8 ppm, η) can be obtained from potentiostatic electroplating result reported in Ref. 46 and the calculated result is shown in Figure 2.…”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation
“…polyalkylene glycols, PAGs) [1,[5][6][7][8][9][10][11], its specific anti-suppressor (bis-(sodium-sulfopropyl)-disulfide, SPS) and a leveler additive (type-II suppressor [5]) dissolved in the Cu(II)-rich plating bath. Particular additive mass transport effects and adsorption kinetics [12][13][14] in conjunction with geometric shape-evolution effects need to be operative during the feature fill [15][16][17][18][19] thus generating a non-uniform surface coverage of PAG suppressors and SPS anti-suppressors. In this way, the suppressing effect of the PAG chemistry is effective predominantly at the upper feature side walls and the 3 topmost wafer surface whereas the SPS accelerated copper deposition occurs preferentially at the feature bottom, thus leading to the desired differential electrodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The additive system, used for PCB electroplating, generally includes accelerator (i.e., bis(3-sulfopropyl) disulfide), inhibitor (i.e., poly (ethyleneglycol)) and leveler (i.e., Janus Green B). [12][13][14][15] The synergy of these additives gives rise to a uniform plating or superfilling in the TH. 9,12 Some literatures indicated that leveler plays an important or decisive role in the accelerator-inhibitor-leveler system.…”
Section: Introductionmentioning
confidence: 99%